Pengaruh Sitokinin, Jenis Eksplan, dan Genotipe terhadap Embriogenesis Somatik Kakao - Nur Ajijah; RR. Sri Hartati (Jurnal Tanaman Industri dan Penyegar, 2016)
Information on the effect of cytokinins on cacao (Theobroma cacao L.) primary somatic embryogenesis and its interaction with explant types and genotypes is not yet known. This study aimed to evaluate the effect of cytokinins and its interaction with explant types and genotypes on cacao somatic embryogenesis. The study was conducted at tissue culture laboratory of IAARD, Bogor from April until December 2012 and October 2014 until February 2016. Three types of cytokinins i.e. kinetin (0.58, 1.16, and 2.32 μM), thidiazuron (0.01, 0.02, and 0.04 μM) and benzylaminopurine (0.55, 1.11, and 2.22 μM) in combination with 9 μM 2,4-D were tested for their effectiveness in inducing somatic embryogenesis from petals and staminoid explants of Cimanggu 1 genotype. Furthermore, three levels of kinetin (0.58, 1.16, and 2.32 μM) also in combination with 9 μM 2,4-D were evaluated for their influences on the somatic embryogenesis from petals and staminoid explants of three cacao genotypes i.e. Sulawesi 02, ICCRI 04 and Cimanggu 3. The result demonstrated that 2.32 μM kinetin and staminoids explant were more effective to induce cacao somatic embryogenesis of Cimanggu 1 genotype (7%, 0.23 embryos/explant). Additionally, there were interaction effects between the level of kinetin with explant types and genotype on the percentage of explants forming embryo at 12 weeks after culture. The highest percentage of somatic embryo formation was shown by ICCRI 04 genotype with the use of petals explant and a kinetin level of 1.16 μM (31.85%), but not significantly different from the level of kinetin 2.23 μM (25.55%). The formation of primary somatic embryos of cacao is largely determined by the type and level of cytokinins, type of explant, and genotype.